Prognostic impact of HPV-associated p16-expression and smoking status on outcomes following radiotherapy for oropharyngeal cancer: The MARCH-HPV project. Issue 1 (January 2018) - Lassen, Pernille; Lacas, Benjamin; Pignon, Jean-Pierre; Trotti, Andy; Zackrisson, Bjorn; Zhang, Qiang; Overgaard, Jens; Blanchard, Pierre; ,
Abstract: Background and purpose: Evaluate the prognostic and predictive impact of HPV-associated p16-expression and assess the combined prognostic impact of p16 and smoking on altered fractionated radiotherapy (AFRT) for oropharyngeal cancer (OPC) within the frames of the update of the Meta-Analysis of Radiotherapy in Carcinomas of Head and neck (MARCH). Materials and methods: Patients with OPC, known tumor p16-status and smoking history were identified from the MARCH update, resulting in a dataset of 815 patients from four randomized trials (RTOG9003, DAHANCA6&7, RTOG0129, ARTSCAN). Analysis was performed using a Cox model stratified by trial and adjusted on gender, age, T-stage, N-stage, type of radiotherapy fractionation, p16, smoking. Primary endpoint was progression-free survival (PFS). Results: In total, 465 patients (57%) had p16-positive tumors and 350 (43%) p16-negative. Compared to p16-negative, p16-positive patients had significantly better PFS (HR = 0.42 [95% CI: 0.34–0.51], 28.9% absolute increase at 10 years) and OS (HR = 0.40 [0.32–0.49], 32.1% absolute increase at 10 years). No interaction between p16-status and fractionation schedule was detected. Smoking negatively impacted outcome; in the p16-positive subgroup, never smokers had significantly better PFS than former/current smokers (HR = 0.49 [0.33–0.75], 24.2% survival benefit at 10 years). Conclusions: No predictive impact of p16-status on response to AFRT could be detected but the strong prognostic impact of p16-status was confirmed and especially p16-positive never smoking patients have superior outcome after RT.